2021
DOI: 10.1007/s10544-021-00547-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic probe-based microrheology reveals local softening and stiffening of 3D collagen matrices by fibroblasts

Abstract: Changes in extracellular matrix stiffness impact a variety of biological processes including cancer progression. However, cells also actively remodel the matrices they interact with, dynamically altering the matrix mechanics they respond to. Further, cells not only react to matrix stiffness, but also have a distinct reaction to matrix viscoelasticity. The impact of cell-driven matrix remodeling on matrix stiffness and viscoelasticity at the microscale remains unclear, as existing methods to measure mechanics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…Further, in contrast to our previous studies 10 and findings by Loeber et al for chondrocytes cultured in a hyaluronic acid gel 44 , stiffness was largely unaffected by distance from the cell, angular position θ , and axes of bead oscillation. Discrepancy in results could potentially stem from the difference in duration of cell culture, as supported by past research that found hydrogel stiffness to vary with cell incubation time 45 , 46 . Reported results are most likely by alternative factors not explored in this project,, including cell seeding density 46 , difference in collagen composition 47 , cell area 48 50 and expression levels of mesenchymal proteins including those for actin, actin polymerization, myosin motors as well as the state of regulatory proteins including ROCK.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in contrast to our previous studies 10 and findings by Loeber et al for chondrocytes cultured in a hyaluronic acid gel 44 , stiffness was largely unaffected by distance from the cell, angular position θ , and axes of bead oscillation. Discrepancy in results could potentially stem from the difference in duration of cell culture, as supported by past research that found hydrogel stiffness to vary with cell incubation time 45 , 46 . Reported results are most likely by alternative factors not explored in this project,, including cell seeding density 46 , difference in collagen composition 47 , cell area 48 50 and expression levels of mesenchymal proteins including those for actin, actin polymerization, myosin motors as well as the state of regulatory proteins including ROCK.…”
Section: Discussionmentioning
confidence: 99%
“…The matrix displacements due to cellular forces are mediated by the local matrix viscoelastic properties; therefore, our technique uses a microscope-integrated system to measure those properties (Figure 2c). This system, a magnetic microrheometer, and its working principle is described in Pokki et al 46 (i.e., system type 2 for stiffer samples 46 ). Briefly, a pair of electromagnets is used to generate sinusoidal magnetic forces onto magnetic probes within the matrix with the cells (Equation S1).…”
Section: ■ Approach To Measuring Protrusive Forces From Cancer Cells ...mentioning
confidence: 99%
“…Further, the methods probe one microscale location at the time. Pokki et al 46 recently introduced a magnetic-microrheology method using matrix-embedded, 10μm-diameter magnetic microspheres that simultaneously probe viscoelasticity of multiple microscale locations inside 3D cultures with stiffness levels as in a developing breast cancer.…”
mentioning
confidence: 99%
“…The tracked displacements were fitted to obtain the amplitude and the phase angle of magnetic-bead motion that allow for the calculation of complex shear modulus (G*) and loss tangent (tan δ) of the hydrogel networks using Equations (S1-S3), Supporting Information. [80] At thermal equilibrium, G* and tan δ are measures of elastic and viscous characteristics of the hydrogel networks that provide insights into the physical/chemical nature of crosslinks in the gel. [81][82][83] As indicated in Figure 2A, all three DNA-AuNR crosslinked networks displayed marked differences in their G* values, when compared to control gels without DNA-AuNR.…”
Section: Thermo-mechanical Characterizationmentioning
confidence: 99%